Ob–Yenisei and Lena plumes: wind–driven dynamics and variability - Savin, Alexander; Osadchiev, Alexander (Frontiers in Marine Science, 2025)
River plumes formed by the Ob, Yenisei, and Lena rivers in the Eurasian Arctic are among the largest river plumes globally in terms of area. In this article, a detailed analysis of newly available satellite-derived surface salinity data retrieved for the Eurasian Arctic is presented. Two dominant spreading types of the Ob–Yenisei plume in the Kara Sea are identified. Under westerly–southwesterly winds, the plume remains coastally trapped along the southern coast of the sea, propagates eastward toward the Vilkitskiy Strait and into the Laptev Sea. Its area scales linearly with the combined Ob–Yenisei river discharge volume. Under easterly–northeasterly winds, the Ob–Yenisei plume expands toward the central and northern Kara Sea. Strong northeasterly winds can drive its advection into the northern part of Kara Sea, with plume areas up to 320 thousand km2. In the Eastern Arctic, the Lena plume exhibits two patterns governed by the presence or absence of wind–driven advection from the Laptev Sea to the East Siberian Sea via the Sannikov and Laptev Straits, controlled by winds over the southeastern Laptev Sea. Within the East Siberian Sea, the Lena plume behaves largely independently and is primarily wind–forced. Its area could exceed 800 thousand km2 and shows weak sensitivity to river discharge volume.